Addressing the Shortage of Fistula Surgeons; up date from FIGO’s Training Initiative - Slinger, Gillian; Trautvetter, Lilli (Nepal Journal of Obstetrics and Gynaecology, 2018)
The FIGO Fistula Surgery Training Initiative has been developed to build the capacities of fistula surgeons in identified training centres using the Global Competency-Based Fistula Surgery Training Manual. Since the launch of the Training Manual in 2011, the project has evolved, and in the last 4 years, has expanded substantially. Coming from 19 fistula affected countries around the world, there are presently 57 trainee fistula surgeons (‘Fellows’) on the Programme, undergoing training placements in established training centres, as well as receiving coaching visits in their home facilities to progressively build their fistula skills and activities over time. While good progress has been made, FIGO recognises and is ready to address the challenges still facing the Programme, and the next exciting phase will include further expansion, with continued admission of Fellows and fistula care teams from selected, high-need countries, while moving towards programmatic consolidation, by further strengthening the skills and activities of Fellows already on the Programme, so that significantly more affected women have access to high quality, life changing fistula treatment.